Dental stigmata and enamel thickness in a probable case of congenital syphilis from XVI century Croatia. Issue 10 (October 2015) - Lauc, Tomislav; Fornai, Cinzia; Premužić, Zrinka; Vodanović, Marin; Weber, Gerhard W.; Mašić, Boris; Rajić Šikanjić, Petra
Highlights We analysed dental remains of an individual with congenital syphilis. The employed methods were macroscopic observation, CBCT and micro-CT scanning. Methods are suitable for recording dental changes and enamel thickness in syphilis.